Old Testament translations in the Grand Duchy of Lithuania and their contexts - Kavaliūnaitė, Gina (Vilnius University Proceedings, 2024)
From the 15th century onwards, the Grand Duchy of Lithuania was a multiconfessional and multicultural state. Apart from Lithuanians, its population comprised Ruthenians (the ancestors of Belarusians and Ukrainians), Poles, and smaller Jewish, Tatar, and Karaim communities. After its Christianization, Lithuania officially fell under the jurisdiction of the Roman Catholic Church, but most of its inhabitants were of the Eastern Christian rite. Reformed Protestantism spread among the nobility at the turn of the 16th and 17th centuries, while Lutheranism flourished in Lithuania Minor. Smaller ethnic groups also had their confessional communities. All confessional groups had their sacred books. This article gives an overview of Christian vernacular translations of the Old Testament that were read in the Grand Duchy between the 15th and the 18th centuries. It briefly discusses the circumstances of the translation of the Old Testament into Ruthenian (the Skaryna Bible), Old Church Slavonic (the Ostrog Bible), Polish (the Brest, Nesvizh and Gdansk Bibles) and Lithuanian (the Bretkūnas, Chylinski and Quandt Bibles) as well as their characteristic features.
Keywords: Old Testament; Grand Duchy of Lithuania; Bretkūnas Bible; Chylinski Bible; Quandt Bible; Skaryna Bible; Ostrog Bible; Brest Bible; Gdansk Bible